2019
DOI: 10.1123/ijsnem.2018-0227
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of Probiotics and Its Effects on Physically Active Individuals and Athletes: Systematic Review

Abstract: The aim of this study was to conduct a systematic review of the effects of probiotic supplementation on physically active individuals. The participants, interventions, comparisons, outcome and study design inclusion criteria were (a) studies involving healthy adults or older subjects of both sexes who did physical exercise (including athletes and physically active individuals), (b) interventions with probiotics, (c) inclusion of a control group, (d) outcomes not previously defined, and (e) clinical trials and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…Interestingly, based on the results of a meta-analysis of randomized controlled trials comparing probiotics with placebo to prevent acute upper respiratory tract infections in children, adults and older people ( n = 3720), Hao et al [163] concluded that probiotics were better than placebo for reducing the incidence of such episodes, the duration of episodes as well as cold-related school absence and antibiotic use. A recent systematic review of the effects of probiotic supplementation on physically active individuals ( n = 1680, athletes and non-athletes) concluded that positive effects were reported for several outcomes including respiratory tract infection, markers of immunity and gastrointestinal symptoms; however, the study failed to identify standardised supplementation protocols owing to the distinct protocols employed across the studies, as well as different measured outcomes and small sample size [164].…”
Section: Impact Of Environment and Life Stage On Gut Microbiota Anmentioning
confidence: 99%
“…Interestingly, based on the results of a meta-analysis of randomized controlled trials comparing probiotics with placebo to prevent acute upper respiratory tract infections in children, adults and older people ( n = 3720), Hao et al [163] concluded that probiotics were better than placebo for reducing the incidence of such episodes, the duration of episodes as well as cold-related school absence and antibiotic use. A recent systematic review of the effects of probiotic supplementation on physically active individuals ( n = 1680, athletes and non-athletes) concluded that positive effects were reported for several outcomes including respiratory tract infection, markers of immunity and gastrointestinal symptoms; however, the study failed to identify standardised supplementation protocols owing to the distinct protocols employed across the studies, as well as different measured outcomes and small sample size [164].…”
Section: Impact Of Environment and Life Stage On Gut Microbiota Anmentioning
confidence: 99%
“…The protective effect of yogurt mainly comes from probiotics (Hao et al 2015;Kok and Hutkins 2018), which have indicated various beneficial effects in protecting the hosts' gastrointestinal and immune systems (Rijkers et al 2010). According to several systematic reviews and meta-analyses of randomized controlled trials, probiotics can be used to prevent and treat URTIs in both children and adults (Wang et al 2016;M€ oller et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Administration of beneficial bacteria by the use of probiotics has been shown to promote mucosal and epithelial health of the gastrointestinal (GI) tract, providing a barrier excluding and eliminating various antigens. Evidence suggests that probiotics are an effective strategy to delay or prevent upper respiratory tract infections [ 1 , 2 , 3 ], reduce indices of GI discomfort during exercise [ 4 ], and improve carbohydrate utilization during prolonged cycling [ 5 ]. While a bulk of the literature regarding probiotics pertains to endurance athletes, data is emerging that suggests that probiotics may provide a benefit in the adaptation and recovery of athletes engaged in resistance or team sport training [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%